You Have the Right to Remain Violent: Police Academy Curricula and the Facilitation of Police Overreach - Lynch, Caitlin (Social justice, 2018)
State and municipal police academies in the United States are intended to provide cadets with the fundamental skills necessary for a career in law enforcement. However, an overwhelming amount of these instructional hours are devoted to preparing prospective police officers to wage war against the communities that they will soon serve, while neglecting topics that may help de-escalate or prevent a potentially violent encounter altogether. This emphasis on such strategies not only exaggerates the dangers associated with policing and contributes to a flawed understanding of the everyday happenings of police work, but it also normalizes the implementation of violent means to resolve conflict. This, in turn, attracts to the profession individuals with mentalities and skillsets consistent with causing harm and potentially discourages or outwardly excludes those who believe these procedures to be at odds with democratic policing.